Tom Clancy red winter [large type] - Cameron, Marc; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel, 2022)
"In 1985 an F117 aircraft crashes into the Nevada desert and the Soviets will do anything to get their hands on its secrets. In East Berlin, a mysterious figure contacts the CIA with invaluable details of his government's espionage plans in return for asylum. It's an offer they can't pass up. With the East German secret police closing in, someone will have to go to behind the Berlin Wall to investigate the potential defector. It's a job Deputy Director James Greer can only trust to one man--Jack Ryan. In enemy territory with an assassin on his tail, can Ryan get the right answers before the Cold War turns into a Red Winter?"--